Ethnobotany of Palau : plants, people, and island culture. compiled and edited by Michael J. Balick and Ann Hillmann Kitalong. - Balick, Michael J., 1952-; Kitalong, Ann Hillmann (New York Botanical Garden, 2020)
'Ethnobotany of Palau' is a two-volume series that examines the relationship between plants, people and traditional culture in the Republic of Palau. Volume 1 contains an introductory chapter on Palau and its environment, followed by chapters on topics including a study of human impact on the landscape; the role of plants throughout Palauan life, from birth to death; the bai, a structure essential to Palauan culture; and the relationship of people to the ocean that surrounds them.